Identifying mïmï as ‘Linseed’ - Russell, Jonny (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
mïmï appears to have diverse applications, appearing in administrative documents, jar labels, depictions of commodity transportation, as well as being used in therapeutic recipes. To date, a consensus for its translation has not been reached. This article re-evaluates the suitability of past identifications in terms of new perspectives in Egyptology, and explores an extended corpus of source material that together suggest a new identification, ‘linseed’, is more appropriate. The hypothesis is further supported through the recreation and discussion of the materiality of ancient Egyptian medical recipes composed of mïmï and other ingredients with secure translations, and demonstrates: 1) that linseed was a commodity which was taxed, stored, and distributed by the ancient Egyptian administration; 2) that the effect of this product upon the body was observed and harnessed in therapeutic medical recipes.